Activity-Based Screening of Soil Samples from Nyingchi, Tibet, for Amylase-Producing Bacteria and Other Multifunctional Enzyme Capacities - Liu, J. H.; Guo, J. N.; Lu, H.; Lin, J. (International Journal of Microbiology, 2022)
Despite the interest in Tibetan soil as a promising source of functional enzymes with potential biotechnological applications, few studies have considered the screening and identification of amylase producing bacteria from Tibetan soil. Amylase has many applications in the food and feed industries, textile and biofuel production, and biomedical engineering. The area of amylase with specific properties is attracting growing attention because of its better application to various industrial conditions. This study aims to screen and identify amylase-producing strains from soil samples collected in Nyingchi, Tibet, and then explore whether the bacterial isolates are superior for unique enzymes. In this paper, a total of 127 amylase producing bacteria were isolated by activity-based screening of six Tibetan soil samples. The 16S rRNA gene survey then identified four major phyla, namely, firmicutes, bacteroidetes, proteobacteria, and actinobacteria, which were differentiated into twelve genera with a dominance of Bacillus (67.72%), followed by Pseudomonas (8.66%). Microbial diversity analysis revealed that the amylase-producing bacterial community of the Kadinggou forest soil sample showed the best variety (the Simpson index was 0.69 and the Shannon index was 0.85). The amylase activity assay of the bacterial isolates showed a mean of 0.66 U/mL at 28°C and pH 5.2. Based on the effect of temperatures and pHs on amylase activity, several bacterial isolates can produce thermophilic (50°C), psychrophilic (10°C), acidophilic (pH 4.2), and alkaliphilic (pH 10.2) amylases. Furthermore, four bacterial isolates were screened for amylase, protease, and esterase activities, which indicated multifunctional enzyme capacities. The present study is expected to contribute to our understanding of Tibetan microbial resources and their potential for scientific research and industrial applications.